2020
DOI: 10.3389/fnins.2020.00161
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Synaptic and Neurochemical Remodeling in the Retina of Aging Degus

Abstract: Accumulation of amyloid-beta (Aβ) peptides is regarded as the hallmark of neurodegenerative alterations in the brain of Alzheimer's disease (AD) patients. In the eye, accumulation of Aβ peptides has also been suggested to be a trigger of retinal neurodegenerative mechanisms. Some pathological aspects associated with Aβ levels in the brain are synaptic dysfunction, neurochemical remodeling and glial activation, but these changes have not been established in the retina of animals with Aβ accumulation. We have em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 66 publications
2
16
0
Order By: Relevance
“…In the South American rodent O. degus, previously reported to develop several spontaneous AD-like pathologies without genetic manipulation, elevated levels of pTau were primarily detected in the GCL to NFL regions of the retina in both adult and aged animals (Du et al, 2015). In a subsequent study by the same group, early punctate AT8 immunoreactivity in the IPL was reported in young degus, compared with the denser expression in IPL to NFL of juvenile and adult animals (Chang et al, 2020). Interestingly, p(tau)-positive aggregates both appeared and propagated to other inner retinal layers earlier than Aβ deposits in these animals (Chang et al, 2020).…”
Section: Alzheimer's Disease Hallmarks In the Retina Of Animal Modelsmentioning
confidence: 83%
See 3 more Smart Citations
“…In the South American rodent O. degus, previously reported to develop several spontaneous AD-like pathologies without genetic manipulation, elevated levels of pTau were primarily detected in the GCL to NFL regions of the retina in both adult and aged animals (Du et al, 2015). In a subsequent study by the same group, early punctate AT8 immunoreactivity in the IPL was reported in young degus, compared with the denser expression in IPL to NFL of juvenile and adult animals (Chang et al, 2020). Interestingly, p(tau)-positive aggregates both appeared and propagated to other inner retinal layers earlier than Aβ deposits in these animals (Chang et al, 2020).…”
Section: Alzheimer's Disease Hallmarks In the Retina Of Animal Modelsmentioning
confidence: 83%
“…In a subsequent study by the same group, early punctate AT8 immunoreactivity in the IPL was reported in young degus, compared with the denser expression in IPL to NFL of juvenile and adult animals (Chang et al, 2020). Interestingly, p(tau)-positive aggregates both appeared and propagated to other inner retinal layers earlier than Aβ deposits in these animals (Chang et al, 2020). Similarly, retinal accumulation of total tau and epitope-specific hyperphosphorylation were also reported to precede onset of behavioral deficits and brain tauopathy as early as 3 months of age in the 3xTg mouse model of AD (Chiasseu et al, 2017).…”
Section: Alzheimer's Disease Hallmarks In the Retina Of Animal Modelsmentioning
confidence: 85%
See 2 more Smart Citations
“…Beyond the brain, a growing number of studies have provided evidence for AD‐specific protein aggregation, vascular pathology, and markers of neuroinflammation in the neurosensory retina of various transgenic, induced, and spontaneous animal models of AD (Chang et al, 2020; Chiasseu et al, 2017; Do et al, 2019; Doustar et al, 2017; Grimaldi et al, 2018; Hampel et al, 2018; Hart et al, 2016; Koronyo et al, 2012; Lei et al, 2017), as well as in human AD patients (Alexandrov et al, 2011; den Haan et al, 2018; Hadoux et al, 2019; Koronyo et al, 2017; Koronyo‐Hamaoui et al, 2011; La Morgia et al, 2016; Schon et al, 2012; Schultz et al, 2020; Shi et al, 2020; Tsai et al, 2014). Biochemical analyses of Aβ 40 and Aβ 42 peptide levels in retinal and brain tissues from several transgenic murine models and AD patients revealed increases in both peptides in the AD retina as compared to controls, with higher levels in the brain and correlations with brain levels (La Morgia et al, 2016; Schultz et al, 2020; Shi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%